No preferential carbon-allocation to storage over growth in clipped birch and oak saplings. (10th February 2020) - Palacio, Sara; Paterson, Eric; Hester, Alison J; Nogués, Salvador; Lino, Gladys; Anadon-Rosell, Alba; Maestro, Melchor; Millard, Peter
Abstract: Herbivory is one of the most globally distributed disturbances affecting carbon (C)-cycling in trees, yet our understanding of how it alters tree C-allocation to different functions such as storage, growth or rhizodeposition is still limited. Prioritized C-allocation to storage replenishment vs growth could explain the fast recovery of C-storage pools frequently observed in growth-reduced defoliated trees. We performed continuous 13 C-labeling coupled to clipping to quantify the effects of simulated browsing on the growth, leaf morphology and relative allocation of stored vs recently assimilated C to the growth (bulk biomass) and non-structural carbohydrate (NSC) stores (soluble sugars and starch) of the different organs of two tree species: diffuse-porous ( Betula pubescens Ehrh. ) and ring-porous ( Quercus petraea [Matt.] Liebl. ). Carbon-transfers from plants to bulk and rhizosphere soil were also evaluated. Clipped birch and oak trees shifted their C-allocation patterns above-ground as a means to recover from defoliation. However, such increased allocation to current-year stems and leaves did not entail reductions in the allocation to the rhizosphere, which remained unchanged between clipped and control trees of both species. Betula pubescens and Q. petraea showed differences in their vulnerability and recovery strategies to clipping, the ring-porous species being less affected in terms of growth and architecture by clipping than the diffuse-porous. These contrasting patterns could be partly explained by differences in their C cycling after clipping. Defoliated oaks showed a faster recovery of their canopy biomass, which was supported by increased allocation of new C, but associated with large decreases in their fine root biomass. Following clipping, both species recovered NSC pools to a larger extent than growth, but the allocation of 13 C-labeled photo-assimilates into storage compounds was not increased as compared with controls. Despite their different response to clipping, our results indicate no preventative allocation into storage occurred during the first year after clipping in either of the species.